Information War Against Moscow State During Time of Troubles: A Case Study of “The Song of the Tyranny of Shuysky” by A. Vladislavsky - N. V. Eilbart (Научный диалог, 2025)
This study investigates the information warfare and propaganda employed by the Polish-Lithuanian Commonwealth against the Moscow State during the Time of Troubles. As an illustration of this issue, the Polish news pamphlet from 1609, "The Song of the Tyranny of Shuysky," housed in the collections of the Russian National Library, is examined. The author provides a complete translation of "The Song..." into Russian for the first time. It is established that this work was authored by the Polish burgher poet Adam Vladislavsky (Wroclawczyk). The analysis highlights that "The Song..." aimed to persuade the inhabitants of the Commonwealth of the righteousness of King Sigismund III's campaign against Smolensk. The study further analyzes contemporary representations of Tsar Vasily Shuysky in the works of his contemporaries. A comparison is made between the accounts of contemporaries (both foreign and Russian) and the text of "The Song of the Tyranny of Shuysky." The findings suggest that the portrayal of the Tsar in "The Song..." is demonized for propagandistic purposes. It is emphasized that cultural and political stereotypes regarding Moscow rulers and the Russian people, originating from Polish-Lithuanian news pamphlets, transitioned to a broader European context, where they persisted for centuries. Echoes of these stereotypes can still be observed in Western propaganda today.